1970
DOI: 10.1037/h0029483
|View full text |Cite
|
Sign up to set email alerts
|

Roles, functions, and training in clinical psychology: A survey of academic clinicians.

Abstract: EW controversies rage in psychology today with more vehemence and diversity of opinion than the matter of goals and program structure in the training of clinical psychologists (Hunt, 1969;Levy, 1962; Rodgers, 1964;Tryon, 1963). This obvious concern led to the "Chicago Conference," at which a number of psychologists deliberated about goals and program structure in the training of clinical psychologists. In their report (Hoch, Ross, & Winder, 1966), the conferees supported the PhD scientist-practitioner model wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
44
0

Year Published

1971
1971
2002
2002

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 13 publications
(14 reference statements)
3
44
0
Order By: Relevance
“…This finding parallels the overwhelming reaffirmation that the model received in a survey of practising psychologists by Thelen and Ewing (1970).…”
Section: Discussionsupporting
confidence: 86%
“…This finding parallels the overwhelming reaffirmation that the model received in a survey of practising psychologists by Thelen and Ewing (1970).…”
Section: Discussionsupporting
confidence: 86%
“…The current findings on this issue in Ph.D. and Psy.D. programs are consistent with earlier research (e.g., Shemberg & Keeley, 1970;Thelen & Ewing, 1970), in that 51% of clinical directors reported emphasis on projectives to be decreased while less than 10% reported a decrease in emphasis on the other five assessment approaches. Moreover, it seems noteworthy that over half of our sample (65%) reported that neuropsychological testing has increased in emphasis in doctoral-level training programs in recent years.…”
Section: Discussionsupporting
confidence: 81%
“…In a survey by Thelen, Varble and Johnson (1968) it was found that academic clinical psychologists regarded projective techniques as declining substantially in use and importance. In a later survey of a similar sample reported by Thelen and Ewing (1970), the respondents favored an emphasis on instruction in research and therapy in lieu of diagnosis.…”
mentioning
confidence: 83%